A stiff collar can restrict atlantoaxial instability in rheumatoid cervical spine in selected cases. Issue 4 (April 1995) - Kauppi, M; Anttila, P
Abstract : OBJECTIVE–To study the efficiency of a stiff collar in restricting the instability of anterior atlantoaxial subluxation (AAS). METHODS–Twenty two successive patients with an unstable AAS were studied. Lateral view radiographs were taken of the cervical spine in flexion, extension, and neutral positions without a collar, and in full flexion with a custom made stiff collar. RESULTS–The collar restricted more than 30% of the maximal instability of the AAS in 50% of the patients. These patients had significantly shorter atlantoaxial distance in the neutral position than those in whom the collar was not able to restrict the instability. CONCLUSION–A stiff collar can restrict the atlantoaxial instability in selected rheumatic patients with an unstable AAS. Lateral view radiographs of the cervical spine in a neutral position can be used to identify the patients whom the collar will benefit.